RELAÇÕES DE GÊNERO E SEXUALIDADE: COMO OS LIVROS DIDÁTICOS DE CIÊNCIAS ABORDAM ESSE TEMA? - Bandeira, Andreia (2018)
The debate on gender relations and sexuality is necessary in Basic Education, and the textbook serves as a subsidy to address this theme. However, its use might be exempt from an adequate understanding, which can lead to the fragility of the education of the student, producing the alienation of these relations in their daily lives. The Science textbook can make it possible to overcome the naturalization of aspects related to gender and sexuality, based on the cis-heteronormative and androcentric social hierarchies. The understanding of gender and sexuality relations as social and cultural constructions produced throughout human history contributes to the debate about diversity and culture in the school space, as well as to the denaturalization of these representations. Thus, this study aims to problematize the way in which gender and sexuality themes are present in Science textbooks, in final years of Elementary School. The curricular content delineated in these materials is the Genital and Reproductive System of the Human Body, being contemplated all the visual resources. It was delimited the analysis of textbooks of all the jurisdictioned schools of the Public State School System of Guarapuava - Pr. The research has the qualitative and quantitative types and follows the criteria of organization of documentary analysis proposed by Laurence Bardin. The historical, cultural and theoretical basis on sexuality, is based on Michel Foucault. For the conceptual support of gender and their relations, the theoretical basis are based on the concepts of Simone de Beauvoir, Joan Scott, Pierre Bourdieu, Judith Butler. Such references are covered by several authors who make the theme interrelated with education, among them Guacira Louro. Science textbooks are transforming and mediating tools in the promotion of sex education. Its incompleteness and disturbing silence point to the importance in discerning the naturalized representations based on the sexist, patriarchal, and cis-heteronormative amalgam and alerting to what is muted in most textbooks.